Implementasi Metode Smart Dengan Menggunakan Sistem Pendukung Keputusan Dalam Menentukan Karyawan Terbaik Pada PT.XYZ: Implementation of the Smart Method Using a Decision Support System in Determining the Best Employees at PT.XYZ - Imam Ahmad; Mohamad Iqbal Suriansyah; Sanusi Sanusi (YCMM, 2021)
Every company that wants to continue to grow and wants to progress, the first thing that needs to be improved is the quality of its human resources. And one way to assess the quality of human resources in the company can be seen from the performance appraisal of employees. The object of this research was conducted at PT. xyz. The research method used in this study is the SMART method (Simple Multi Attribute Rating Technique), because the smart method can solve the problem of making choices that are multi-criteria and with simple analysis compared to other decision-making methods. This performance appraisal system is designed using PHP and MySQ. The method used in system development is the Object-Oriented Analysis and Design (OOAD) method and uses Unified Modeling Language (UML) modeling. The results achieved in the form of a decision support system in determining the best employees at PT.XYZ.